Prediction of asthma using a four-locus gene model including IL13, IL4, FCER1B, and ADRB2 in children of Kazak nationality - Shasha Bai; Jun Lu; Li Hua; Quanhua Liu; Mengxue Chen; Yutong Gu; Jianhua Zhang; Dongjun Ma; Yixiao Bao (BMC, 2023)
Abstract Background To study whether the four locus gene model consisting of ADRB2 rs1042713, IL4 rs2243250, FCER1B rs569108 and L13 rs20541 can predict asthma of the Kazak children in Xinjiang, China. Methods Four single nucleotide polymorphisms about the 4 genes were genotyped in asthma group and control group of Han children and Kazak children respectively. The frequencies of different genotypes and alleles were compared between the asthma group and the control group in the two nationalities. Different risk genotypes for asthma were evaluated in the two nationalities. Results The differences about frequencies of genotypes in ADRB2 rs1042713 and IL4 rs2243250 and IL13 rs20541 between asthma group and control group were statistically significant in Han children, as were the frequencies of alleles in the 3 single nucleotide polymorphisms, but there were no statistical differences in FCER1B rs569108(P > 0.05). For the Kazak children, no differences were existed among all the genotypes and alleles in asthma group and control group. For the Han children, more children were asthma high risk genotype in the asthma group than those in the control group and no difference was found in the Kazak children. Conclusions The four locus gene model consisting of ADRB2 rs1042713, IL4 rs2243250, FCER1B rs569108 and L13 rs20541 can predict asthma of Han children but not for the Kazak children in Xinjiang, which illustrating that the difference of asthma prevalence between different races is closely related to the genetic background.